TRADITIONS OF ENGINEERING ACTIVITY AND SUCCESSFUL INNOVATION STRATEGIES OF MODERN GERMANY - Онопрієнко, В. І.; Онопрієнко, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Germany’s innovative strategy, which has deep historical traditions, is effectively incorporated into state policy and the global economy, seeks to give humane and democratic accents to innovative activities.